1997
DOI: 10.1161/01.hyp.29.3.822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Sodium and Magnesium on Cyclosporin A–Induced Hypertension and Nephrotoxicity in Spontaneously Hypertensive Rats

Abstract: Arterial hypertension, nephrotoxicity, and magnesium loss are common side effects of the immunosuppressive agent cyclosporin A (CsA). In the present study, the effects of dietary sodium and magnesium on CsA toxicity were examined in spontaneously hypertensive rats. A 6-week treatment with CsA during a moderately low-sodium diet (Na 0.3%, Mg 0.2% of the dry weight of the chow) raised blood pressure only slightly, without evidence of nephrotoxicity. By contrast, CsA during a high-sodium diet (Na 2.6%) produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 30 publications
0
34
1
Order By: Relevance
“…21 In SHR, this exact CsA regimen produces a final tissue concentration of CsA in the heart that is almost 4 times higher than in the skeletal muscle. 20 Our results differ from those of Sussman et al 11 who reported that systemic CsA virtually eliminated LVH not only in several transgenic mouse models of sarcomeric disruption but also in rats with aortic banding. Whereas the study of Sussman et al 11 focused mainly on transgenic mouse models of dilated cardiomyopathy, our study provides a more comprehensive examination of pressure-overload hypertrophy in rats.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…21 In SHR, this exact CsA regimen produces a final tissue concentration of CsA in the heart that is almost 4 times higher than in the skeletal muscle. 20 Our results differ from those of Sussman et al 11 who reported that systemic CsA virtually eliminated LVH not only in several transgenic mouse models of sarcomeric disruption but also in rats with aortic banding. Whereas the study of Sussman et al 11 focused mainly on transgenic mouse models of dilated cardiomyopathy, our study provides a more comprehensive examination of pressure-overload hypertrophy in rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The age of 5 weeks was chosen because this predates the onset of hypertension and LVH in SHR. 19,20 At the 6-week end point, rats were anesthetized with methohexital sodium (Eli Lilly; 50 mg/kg IP). A catheter was inserted into the left carotid artery and tunneled subcutaneously to exit from the nape for subsequent measurements of arterial pressure in the conscious state.…”
Section: Protocol 1: Effects Of Csa On Lvh In Shrmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence from animal, epidemiological, and clinical studies suggests that a high dietary salt intake is associated with myocardial hypertrophy. [2][3][4][5][6] Although the mechanism of salt-induced myocardial hypertrophy is poorly understood, dietary salt intake is thought to modify the process of myocardial hypertrophy by hemodynamic and/or nonhemodynamic mechanisms. 7 The development of cardiac hypertrophy in response to pressure and/or volume overload is generally considered to be an adaptive mechanism to normalize ventricular wall stress.…”
mentioning
confidence: 99%
“…Animal studies [27][28][29] have concluded that a low sodium intake may amplify the nephrotoxic effect of cyclosporine. However, these studies examined the effect of sodium depletion rather than a moderate sodium restriction and cannot be applied to human low sodium diets.…”
Section: Adverse Effects Of Restricted Sodium Intakementioning
confidence: 99%